(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2020)
Grape (Vitis vinifera L.) is globally cultivated as commercial fruit crop usually used for fruit purpose or industrial product. The objective of the current review is to review and identify the research gap on the effect of different growth media and vitrification on shooting and rooting performance of grape. Factors affecting rooting of grape cuttings can be internal or external factors. Currently, grapevines are very sensitive to disease in the conventional method of propagation. Even if tissue culture is recommended for healthy propagation of the grape varieties, still factors affecting the growth of the plant verifications were reported. This, review paper progressively revised for the existing factors and possible solutions during in vitro propagation of grapevines. Int. J. Agril. Res. Innov. Tech. 10(1): 1-5, June 2020